INQUIRY BASED WORKSHEET DEVELOPMENT ON SELVOLTA EXPERIMENT KIT - Fithri Fajri Aisyah; Ida Farida; Citra Deliana Dewi S (Gunung Djati Conference Series, 2021)
This research is driven by the importance of visual learning media to improve the ability to understand chemical concept involves three levels of chemical representation in Voltaic cell material. This research uses the Desain Based Research method stages with a stage of analysis, design, and development to produce small-scale experiments and the Voltaic cell model. Based on this research results, the product is obtained using a Voltaic cell model kit with the characteristics of combining macroscopic, submicroscopic, and symbolic representations with guidebooks and worksheets. Validation results indicate that the product is valid with the acquisition of the value of count on the worksheet of 0,83 and props of 0.85 to be used in learning Voltaic cell.